Development of antioxidant-rich cocoa liquor mask for skin rejuvenation - Abd Halim, Alyaa Nurathirah (2021)
Halal cosmetics generally derive from plant-based materials. Cocoa liquor (CL), a paste produced from ground cocoa (Theobrama cacao L.) beans, is a natural source of antioxidants with high potential health benefits. The present study was conducted to determine the prospect of incorporating CL in skin care cosmetics, complementing its ability in protecting the skin by warding off free radicals from the environment. Polyphenols and methylxanthines in CL extract were assayed using Liquid Chromatography-Mass Spectroscopy (LC-MS/MS). In formulating cocoa facial mask (CFM), the chemical components in each ingredient were analyzed and characterized in terms of either thickness or watery texture. The final formulation was optimized and characterized by pH, rheology, texture and color measurements. In accelerated stability, freeze-thaw cycles and centrifuge studies were conducted to determine the stability of CFM in the parameters under study. The CFM was determined of its antioxidant activities including total phenolic content (TPC), total flavonoid content (TFC), 1,1- diphenyl-2-picryhdrazyl (DPPH), Ferric Ion Reducing Power (FRAP) and β-carotene linoleate bleaching (β-CB). Results showed that TPC and TFC were recorded at 131.97±0.06 mg GAE/g and 4.10± 0.0 mg RE/g dried weight of sample, respectively. DPPH free radical scavenging activity was observed at the highest concentration of 87.99± 0.03 % with EC50 of 30.33± 0.0 mg/mL. The FRAP reading was recorded at 252.31 ± 0.001 mmol Fe2+/g dry weight at 1000 mg/mL. The β-carotene linoleate bleaching (β-CB) assay was detected at the highest concentration of 83.42 ± 0.03 % with EC50 of 2.92 ± 0.03 mg/mL. In microbiological studies, oven, room temperature and chiller treatments recorded microorganism growth of 1.0 x 101 cfu/g, < 1 cfu/g and < 1cfu/g on Day 28, meanwhile yeast and mould growth yield were recorded at < 10 cfu/g for all treatments. Heavy metals such as arsenic, lead, cadmium and mercury were detected below the range as suggested by ASEAN. Eye and skin irritation tests depicted the CFM irritant in eye and non-irritant in skin applications. The efficacy of the CFM was measured by in-vitro. The CFM acted as good natural inhibitors in collagenase, tyrosinase and elastase activities on the skin. The study presented scientific validation on phytochemical contents of CL showing presence of bioactive compounds with nutritional and therapeutic values which had positive impact on skin health due to the cocoa butter contained in CL, suggesting its prospective use in value-added products such as skin care cosmetics.